الدفع بعدم الدستورية في ظل التعديل الدستوري 2020 - مي زعراء, سلامة (جامعة الوادي.University eloued, 2021)
"أدرج المؤسس الدستوري الجزائري بموجب التعديل الدستوري الجديد لسنة 2020 في مجال الرقابة على دستورية القوانين، الرقابة اللاحقة عن طريق الدفع بعدم دستورية الأحكام التشريعية ضمن النص المعدل في القانون الدستوري الجديد، والتي تعد تأسيس دستوري لهذه الرقابة، التي تسمح للمتقاضي إثارة عدم دستورية الحكم التشريعي الذي طبق على النزاع المطروح أمام الجهة القضائية التي تقوم بدورها بالبت في هذا الدفع إما برفضه أو قبوله، وإحالته على الجهات القضائية العليا (المحكمة العليا أو مجلس الدولة) التي تتكفل بعملية غربلة وتصفية طلبات الدفع في المدة القانونية المحددة من طرف المشرع، وبذلك يتم تحديد مصير طلب الدفع في الاتصال بالمجلس الدستوري من عدمه. ويتولى المجلس الدستوري صلاحية البت في الدفع في أجل أربعة أشهر قابلة للتجديد مرة واحدة، وفي حالة ما إذا تم التصريح بعدم دستورية الحكم التشريعي محل الدفع بعدم الدستورية، فان ذلك يؤدي إلى إلغائه وفقدانه من النظام القانوني مما يجعل الجهة القضائية المعنية بالفصل في الدعوى الأصلية تواصل عملها بعد استبعاد ذلك الحكم التشريعي الملغى، ذلك أن القرار الذي اتخذه المجلس الدستوري يكتسي القوة الإلزامية في مواجهة الجميع باعتبار أن قرارات المجلس الدستوري تتمتع بالحجية المطلقة.er the new constitutional amendment of 2020 in the field of oversight on the constitutionality of laws, included the subsequent oversight by pleading for the unconstitutionality of legislative provisions within the amended text in the new constitutional law, which is a constitutional foundation for this oversight, which allows the litigant to raise the unconstitutionality of the legislative provision that It is applied to the dispute submitted to the judicial authority, which in turn decides on this payment, either by rejecting it or accepting it, and referring it to the higher judicial authorities (the Supreme Court or the State Council), which undertakes the process of sifting and liquidating the payment requests within the legal period specified by the legislator, and thus the fate of the fate is determined Requesting payment to contact the Constitutional Council or not. The Constitutional Council has the authority to decide on the payment within a four-month period, renewable once. Its action is after excluding that repealed legislative provision, because the decision taken by the Constitutional Council has mandatory force in the face of all, considering that the decisions of the Constitutional Council enjoy absolute authority. " "
ماستر قانون إداري
Keywords: التعديل الدستوري 2020 - الدفع بعدم الدستورية - المؤسس الدستوري - المشرع الجزائري - المحكمة الدستورية